G-20 SUMMIT 2022 LESSON LEARNED: THE DEFENSE DIPLOMACY LENSES - Rui Duarte; Anak Agung Banyu Perwita; Jonni Mahroza; Herlina Juni Risma Saragih; Editha Praditya; Riant Nugroho (Universitas Jenderal Ahmad Yani, 2023)
As the president of G-20 in 2022, Indonesia held the Summit of 19 countries plus one region, representing 80% of the world's GDP, 75% of global exports, and 60% of the global population. Indonesia's interests in G-20 Bali were on strategic and direct appeal. The strategic benefits were (a) taking G 20 as a strategic forum to discuss global issues: global health, financial stability, and climate change, (b) showcasing Indonesia's economic recovery efforts during the Covid-19 pandemic, and (c) showcasing Indonesia's role as a meeting leader that will support the formation of global policies. The immediate benefits were (a) an increase in foreign exchange from delegation visits to Indonesia, (b) a revival of the hospitality sector, (c) support for the increase in domestic consumption, (d) optimising the role of MSMEs, and (e) increase employment absorption. Using the defence diplomacy lens instrument, the research found that the Summit has reached a profound performance, as the total commission is reaching 3,89 from 4.00. The economic interest of the nation has been delivered at the score of 3.66, which means the level of defence diplomacy has almost reached the 4th level –the regulator—which puts Indonesia as a very high-impact country. The political interest was delivered at the score of 2.00, which means the performance level was facilitator, the ow impact country. The general interest was shown at a 3.00 score, which means the negotiator, which means that Indonesia might have been a high-impact country.